Comparative study of in situ polymerized waterborne polyurethane/nano-silica composites and polyethersiloxanediol-modified polyurethane. (January 2017) - Yan-ting, Han; Zheng, Cheng; Wei, Dong; Fan, Zhang; Zhong-yin, Xin
The waterborne polyurethane/nano-silica composites (WPU/nano-silica, WPUS) and WPU composites modified by polyethersiloxanediol (WPUPES) were prepared, respectively. The properties of WPUS and WPUPES were investigated by various characterizations. The results showed both WPUS and WPUPES had better waterproof property and thermal stability than neat WPU. However, WPUPES has a lower elongation at break due to the higher micro-phase separation. This is ascribed to migration and aggregation of siloxane segments during the film formation. The tensile strength of WPUS was higher than that of neat WPU. This is attributed to the WPUS chain restriction caused by the network and physical cross-link points of nano-silica particles. Moreover, the glass transition temperature of WPUS shifted to higher temperature region while that of WPUPES shifted to lower temperature region.